2008
DOI: 10.4103/0019-5278.40810
|View full text |Cite
|
Sign up to set email alerts
|

An ergonomic study of women workers in a woolen textile factory for identification of health-related problems

Abstract: The observational cross-sectional study conducted on a sample of 100 women workers who volunteered, outlines their cardio-respiratory and musculo-skeletal profile before, during and at end of work. In addition, information on their health status in general was collected in advance.Contrary to expectation, there was no significant change in respiratory function. However, the musculo-skeletal problems were found to be abundantly present with pain in 91% of the subjects. Region-wise mapping of pain revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 8 publications
1
26
0
1
Order By: Relevance
“…Knutsson [10] also provides a model to summarize possible mechanisms of disease in shift workers. Metgud et al [11] conducted an observational cross-sectional study of a sample of 100 women workers with respect to their cardio-respiratory and musculoskeletal profile before, during and at the end of the work. Sant et al [12] have studied the adverse effect of smoke/flue on lung functions of glass factory workers of Firozabad district.…”
Section: Introductionmentioning
confidence: 99%
“…Knutsson [10] also provides a model to summarize possible mechanisms of disease in shift workers. Metgud et al [11] conducted an observational cross-sectional study of a sample of 100 women workers with respect to their cardio-respiratory and musculoskeletal profile before, during and at the end of the work. Sant et al [12] have studied the adverse effect of smoke/flue on lung functions of glass factory workers of Firozabad district.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was conducted on carpet weavers by Choobineh et al [19] who studied the prevalence of MSD symptoms in different body regions and showed that shoulders (47.8%), lower back (45.2%), wrists (38.2%), upper back (37.7%), neck (35.2%) and knees (34.6%) were the most commonly affected regions among the weavers. Metgud et al [20] also studied on the MSD of women workers in a woolen textile factory and reported occurrence of pain in the lower back (47%) and neck (19%). In a study on handloom weavers [21] it was reported that the occurrence of MSD was high in lower back (75%), upper back (73.4), shoulder (68%) , elbow (65%), wrist (70.3%), and neck (57.8%).…”
Section: Discussionmentioning
confidence: 99%
“…An industry is identified in central India, where operators are mostly women operators and 91% of them are suffering from work related MSDs [3].…”
Section: Introductionmentioning
confidence: 99%
“…due to frequent bending posture while cutting firewood in repetitive motion, carrying heavy loads, forceful exertion etc. Majority of the subjects involved in repetitive nature of work had shoulder and wrist pain which may lead to Cumulative Trauma Disorder (CTD) in long run [26,27]. Pain in the lower back can restrict mobility and interfere with normal functioning.…”
Section: Perceived Health Hazardsmentioning
confidence: 99%